Arylbiamidines: synthesis and structural studies en route to anticancer applications. (3rd June 2021) - Grytsai, Oleksandr; Gonçalves, Leticia Christina Pires; Bardovskyi, Rostyslav; Hamouda-Tekaya, Nedra; Rocchi, Stéphane; Ronco, Cyril; Benhida, Rachid
Abstract : Four novel arylbiamidine series were studied showing particular tautomerism and H-bonding structure highlighting their promising druglike features toward anticancer applications. Abstract : Biamidines are a unique and poorly studied class of nitrogenous compounds prone to tautomerization and H-bonding. Four series of heteroaryl diarylbiamidines were synthesized and the antimelanoma activity and physicochemical properties of the resulting 37 new compounds were evaluated. The dimethylthiazolyl 3-bromophenyl biamidine derivative B6 inhibits the growth of six different melanoma cell lines, having higher activity than the positive control drug, the B-RAF inhibitor PLX4032. This study introduces diarylbiamidines as promising frameworks for drug discovery.